PENGARUH PENGAWET KARBOKSIMETIL KITOSAN PADA BAKSO IKAN KURISI (Nemipterus japonicus) PADA PENYIMPANAN SUHU RUANG - Khutwah, Rahma Malmus Fatin; Haryati, Sakinah; Aditia, Rifki Prayoga (Leuit (Journal of Local Food Security), 2024)
Japanese threadfin bream is one the low economic fish which is quite abundant in Banten Province but utilization of its product processing is still not optimal. One of the fishery product that can be made is fish meatballs. This study aims to determine the optimal concentration of carboxymethyl chitosan in Japanese threadfin bream meatballs during room temperature storage. This research used a completely randomized 2 factorial and 2 replications. The first factor is the CMC concentration which consists of 4 levels, namely 0%, 1%, 2% and 3%. The second factor is storage time which consists of 5 levels, namely days 0, 1, 2, 3 and 4. The research results showed that the use of 1% CMC could increase the shelf life of meatballs by 2 days based on the Total Plate Count (TPC), pH, organoleptic test and physical test.